O impacto da migração sobre as mudanças nas estruturas etárias da Região Nordeste e dos estados de São Paulo e Minas Gerais: 1970 a 2010 - Luana Junqueira Dias Myrrha (2014)
The main purpose of this study was to estimate the effect of migration in the aging process of the Northeast region and in the states of São Paulo and Minas Gerais, regarding a long and a medium term. In the long-term analysis (1970-2010), we compared the change in average population age observed with what each population would experience if it was closed to migration. The results show that migration contributed 18% and 7% of the increase in the average age of Northeast and Minas Gerais, respectively. . For São Paulo the effect of migration was rejuvenating, since the variation of the average population age was 13% less than it could be if population was closed to migration. In the medium term (1986-1991, 1995-2000 and 2005-2010) the effect of migration in relation to the effect of birth and death on the population aging process of the three study populations have been analyzed through an adaptation to the model proposed by Preston et al (1989). As expected, the migration was the component with the lowest impact to São Paulo and Minas Gerais. And the effect decreased with time Otherwise for the Northeast region it remained almost constant. To better understand this behavior, it was proposed a detailing on the effect of migration on the basis of the characteristics of migration flows, its intensity, its selectivity by sex and age, and their origins. Although the migration component has not shown a major role in the aging process, migration flows are presented as an important factor to be incorporated in studies on aging, especially in small populations, whose fertility and mortality functions tend to stability. In such context the amplitude of variation of vital events does not present the same potential that migration can take in the future.